Effects of ocean acidification on the socio-ecological system of mitiliculture in southern Chile: Market impacts and challenges for future sustainability under hypothetical models - San Martín Montoya, Valeska Andrea (2019)
The effects of global change are modifying the fundamental characteristics of the oceans, generating variations in different physical-chemical parameters (e.g. temperature, salinity, oxygen, pH, among others). Greenhouse gas models indicate that an evident increase in the levels of atmospheric carbon dioxide (CO2) and, consequently, in the partial pressure of CO2, is leading to a decrease in pH in seawater, a process known as Acidification of the Ocean (AO). The AO is presented as one of the most important threats to the group of marine populations and ecosystems. Fishing and aquaculture are considered activities of economic and social importance, as well as being sources of protein, energy and essential nutrients, representing food security for a future human population in constant growth. In this context, several studies have focused on determining the effect on biological responses under the new conditions of global change in the oceans, but most of these studies have not considered the direct relationship that exists between species of commercial importance and the possible impact on the market, and may even have important repercussions for producers and consumers. This proposal intends to establish a transdisciplinary effort to reduce these gaps in the understanding of environmental effects in species of commercial importance, which could affect the economy and human well-being. The objective of this thesis is to evaluate the effect of exposure to a future AO scenario in the early and late development of the commercial species Mytilus chilensis, determining its sensitivity and possible variations in physical attributes (shell color and hardness) and nutritional (Omega3 fatty acids EPA and DHA, Vitamin B12 and proteins), which are defined as market indexes with possible effects on supply and demand. Along with the above, this study will contribute with the exploration and projection of the adaptive potential present in the mussel farming companies to face the consequences of global change. The methodological ...